Biallelic COL3A1 mutations result in a clinical spectrum of specific structural brain anomalies and connective tissue abnormalities. Issue 9 (25th July 2017) - Horn, Denise; Siebert, Eberhard; Seidel, Ulrich; Rost, Imma; Mayer, Karin; Abou Jamra, Rami; Mitter, Diana; Kornak, Uwe
Abstract : Vascular Ehlers–Danlos syndrome (type IV) is an autosomal dominant disorder caused by heterozygous variants of COL3A1 . We identified biallelic COL3A1 variants in two unrelated families. In a 3‐year‐old female with developmental delay the nonsense variant c.1282C>T, p.(Arg428*) was detected in combination the c.2057delC, p.(Pro686Leufs*105) frame shift variant. Both compound heterozygous variants were novel. This patient was born with bilateral clubfoot, joint laxity, and dysmorphic facial features. At the age of 2 years she developed an aneurysmal brain hemorrhage. Cerebral MRI showed a peculiar pattern of profound cerebral abnormalities including bilateral frontoparietal polymicrogyria of the cobblestone variant. In the second family, the two affected siblings were homozygous for the missense variant c.145C<G, p.(Pro49Ala) of COL3A1 and showed cobblestone‐like cortical malformation, cerebellar cysts, and white matter abnormalities, developmental delay, and seizures. To date, three further families have been reported with biallelic variants of this gene and specific structural brain anomalies in all, and a severe Ehlers–Danlos syndrome phenotype in some. Bilateral frontoparietal polymicrogyria of the cobblestone variant, cerebellar microcysts, and abnormalities of the white matter characterize this brain phenotype and resemble neurological manifestations in individuals with autosomal recessive mutations in GPR56, which serves as a ligand of COL3A1 . In concordance with the findings in knock out mice, the collagen III protein plays a role in the regulation of cortical development in addition to its well‐known function in connective tissue formation.